Use of the Health Information Pack Program (HIPP) in Adolescent Girls with Anaemia - Marliany, Heni; Faujiah, Diny Nur; Nurhayati, Nurhayati; Anwar, Syamsul; Anggraini, Dewi; Khasanah, Uswatul (GLOBAL HEALTH SCIENCE GROUP, 2024)
The Health Information Package Program (HIPP) is a structured and planned health education programme that has been shown to be effective in increasing knowledge, adherence to iron supplementation, food choices and Hb levels in people with anaemia. This study aims to determine the effect of HIPP implementation on adolescent girls with anaemia in SMAN 2 Ciamis. Method: This study is a quantitative study with Quasy experimental design one group pre-post design. The population of this study were all adolescents suffering from anaemia at SMA Negeri Ciamis as many as 98 people. The sampling technique used purposive sampling and obtained 30 respondents. This research was conducted for 2 months from December 2023 to January 2024. The research instruments used were questionnaires which has been tested for validity and reliability, mobile phones and observation sheets. Data analysis was done using univariate and bivariate techniques with paired t-test. The results showed that students' knowledge about anaemia had a p-value of 0.330 > 0.05, students' ability to choose food had a p-value of 0.738 > 0.05, students' compliance with taking TTD had a p-value of 0.000 < 0.05, students' Hb values had a p-value of 0.009 < 0.05. There is a significant effect of HIPP implementation on adherence to taking blood supplement tablets and Hb levels, but this study also shows no effect of HIPP implementation on knowledge and ability to choose foods.